Integration of Pharmaceutical Science in the Education of Healthy and Functional Food Preparation at SMK Negeri Pantai Labu (JURNAL PENGMAS KESTRA (JPK), 2025)
The modernization of lifestyle among today’s adolescents has led to significant changes in daily consumption patterns. Many teenagers tend to prefer fast food that is high in sugar, salt, and fat, but low in nutritional value. This condition may lead to various long-term health problems if not accompanied by adequate nutritional education and awareness. This community service activity aims to integrate pharmaceutical science concepts into the education of healthy and functional food preparation at SMK Negeri Pantai Labu. The implementation method consisted of several stages: initial observation of students’ knowledge and habits, delivery of interactive educational materials, hands-on practice in preparing functional food products, and evaluation through pre-test and post-test instruments. This activity involved 30 students from the culinary arts department. Evaluation results showed a significant improvement across all aspects: knowledge of healthy food increased from 55.0 to 85.3; understanding of functional food from 47.5 to 82.0; understanding of active compounds from 41.2 to 78.5; food preparation skills from 50.4 to 80.6; and awareness of food safety from 52.8 to 86.7. The average overall improvement reached 67.3%. This community service activity concludes that an educational approach based on pharmaceutical science, when applied through culinary practice, is proven to be effective in enhancing students’ competencies, not only in terms of academic knowledge and health awareness but also in fostering entrepreneurial potential in the field of local food.